Hyperglycaemia in comatose survivors of out-of-hospital cardiac arrest. Issue 5 (August 2018) - Russo, Juan J; James, Tyler E; Hibbert, Benjamin; Ramirez, F Daniel; Simard, Trevor; Osborne, Christina; Bernick, Jordan; Wells, George A; Le May, Michel R; ,
Background: The optimal blood glucose target during the early hospitalisation of comatose survivors of out-of-hospital cardiac arrest (OHCA) has not been established. Methods: In a retrospective cohort study, we examined clinical outcomes in relation to mean blood glucose during the first 96 hours of hospital admission in comatose survivors of OHCA with an initial shockable rhythm. Mean blood glucose was assessed as a continuous (primary analysis) and categorical variable: <6 mmol/L, 6 to <8 mmol/L and ⩾8 mmol/L. Co-primary outcomes were the rates of death during the index hospitalisation and severe neurological dysfunction at discharge. We used multivariable logistic regression analyses to adjust for baseline differences in patient and index event characteristics. Results: Among 122 eligible patients, death and severe neurological dysfunction occurred in 29 (24%) and 40 (33%) patients, respectively. Higher mean blood glucose levels during the first 96 hours of admission were associated with increased odds of death (odds ratio (OR): 1.50; 95% confidence interval (CI): 1.17–1.92; p = 0.001) and severe neurological dysfunction (OR: 1.42; 95% CI: 1.11–1.80; p = 0.004). The associations between mean blood glucose and the odds of death (OR: 1.35; 95% CI: 1.04–1.76; p = 0.02) and severe neurological dysfunction (OR: 1.28; 95% CI: 1.00–1.64; p = 0.05) persisted after adjusting for age, time from cardiac arrest to return of spontaneous circulation (ROSC) and vasoactive agent use. There was no interaction between age, time from cardiac arrest to ROSC or a history of diabetes mellitus and the relationship between mean blood glucose and co-primary outcomes. Conclusions: In comatose survivors of OHCA with initial shockable rhythms, higher mean blood glucose levels during the first 96 hours of admission are associated with increased rates of death and severe neurological dysfunction.